Nasal Reconstruction: Current Overview. (December 2018) - Fernandes, Justin R.; Pribaz, Julian J.; Lim, Alan A.; Guo, Lifei
Abstract : Abstract: The nose, with its conspicuous location, intricate convexities, and delicate 3-dimensional structure, continues to challenge the reconstructive surgeon. Today, there are a myriad of options available for reconstruction. The practitioner must take into account the location of the defect as well as the components needed to be restored. This article addresses the current practices in nasal reconstruction, including the different strategies for skin coverage, nasal lining, and structural support. We discuss both the newest techniques as well as basic principles of this long-standing procedure.